Designing and Evaluating the Usability and Onboarding for a Mixed-Reality Application: A Case Study with PEARL (Paderborn Electrical Engineering AR Laboratory) and Meta Quest 3 - Alptekin, Mesut; Münstermann, Daniel; Temmen, Katrin (Lecture Notes in Networks and Systems)
Abstract This study explores the usability and onboarding process of a Mixed Reality (MR) application called PEARL, designed to prepare students for laboratory work. Originally developed for mobile Augmented Reality (mAR), PEARL was adapted for MR to offer a more immersive and intuitive experience through hand and gesture controls. Since many students lack experience with MR devices, a user-friendly onboarding system is essential. The study aims to redesign PEARL’s user interface and onboarding experience, evaluating how intuitive interaction elements impact usability. First, a literature review will identify existing usability guidelines for MR applications, which will guide the redesign of the interface. This new version will then be tested with students through a user study. Feedback will be collected via an online survey to assess the onboarding and user experience, and the findings will be used to refine the design further. The expected outcome is an improved onboarding process and interface, making PEARL accessible even for MR novices, enhancing their ability to interact with 3D objects in a real-world setting. Ultimately, the study aims to provide best practices for developing intuitive MR interfaces and effective onboarding experiences, especially in educational contexts.
Keywords: Meta Quest 3; Augmented Reality; Mixed Reality; PEARL; Electrical Engineering; Laboratory Training; Onboarding; User Experience; User Interface; Heuristics

Einfluss der Berufserfahrung von Multiplikatorinnen und Multiplikatoren auf die Wirksamkeit von Fortbildungsmaßnahmen zur frühen mathematischen Bildung. Zeitschrift Für Erziehungswissenschaft - Hagena, Maike; Bruns, Julia; Gasteiger, Hedwig (Zeitschrift für Erziehungswissenschaft)
Teachers expect facilitators to have own teaching experience as a teacher in order to be able to carry out effective teacher professional development programs. As part of the project EmMa(M), it is investigated, to which extent the teaching experience of facilitators influences the development of early childhood teachers' (n = 83) mathematical pedagogical content knowledge (MPCK) and early childhood teachers' enjoyment of mathematics in the context of a teacher professional development program. It turns out that the teaching experience of the facilitators has no influence on the development of early childhood teachers' MPCK, but favors the development of early childhood teachers' enjoyment of mathematics. Controlling for this increased enjoyment an influence of teaching experience on the development of early childhood teachers' MPCK emerges, but in favor of the participating facilitators who have no teaching experience but have a university degree.
Keywords: Facilitator professional development; Early childhood teachers; Teaching; experience; Early mathematics education

Du Châtelet, Émilie (1706–1749) - Hagengruber, Ruth (Encyclopedia of Early Modern Philosophy and the Sciences)
Of the many outstanding female philosophers of the European Enlightenment, Emilie Du Châtelet excelled as a physicist, a philosopher, and a mathematician, as well as a Bible critic. She was famous in her lifetime and was not completely forgotten thereafter. Among her admirers, correspondents and friends were the most acknowledged scholars of her time, including Voltaire, Clairault, Maupertuis, Diderot, Helvetius, La Mettrie, Buffon, Christian Wolff, Leonard Euler, and Johann II Bernoulli. Her philosophical work enjoyed high reputation and her opus magnum, the Institutions physiques, was translated into Italian and German and proved her to be an intellectual of European stature. Its defense of living forces and its implied forecast into dynamics as well as her methodological grounding of scientific knowledge as hypothetical, impacted philosophy and science. Reality must by nature escape us. What we perceive are phenomena. Du Châtelet explains the function of space and time to trace us back to the origin of phenomena. Her influence on Kant is evident. Next to her writings in physics, mathematics, philosophy, language, and logic, she contributed to morality and ethics. Du Châtelet left an opus of quite systematic breadth. This impressive publishing activity excels in the amount of its scientific and philosophical production to which a vast collection of manuscripts must be added.She argued against prejudice and idolatry in philosophy and science. Science is a cooperative undertaking over history and beyond nations. Her moral writings align with ideas of the French materialists. Du Châtelet translated and commented on Newton’s Principia, preparing thus the fertile soil of the generation of physicists to come in France.
Keywords: aura Bassi Luise Gottsched Immanuel Kant Dourtous de Mairan Johann II Bernoulli Algarotti Buffon d’Alembert La Mettrie Principle of contradiction Hypotheses Enlightenment Leibniz-Clarke Correspondence Living forces Dead forces; happiness Space Imaginary beings Monads Epicurus Ethics Women philosophers Newton’s laws Principia Motion inertia Active force Vis viva Vis mortua Hypothetic reasoning Hypotheses; a priori principles; Experience; Dead forces; Living forces; Energy Dynamics

“Service Encounter 2.0”: An investigation into the roles of technology, employees and customers - Larivière, Bart; Bowen, David; Andreassen, Tor W; Kunz, Werner; Sirianni, Nancy J; Voss, Chris; Wünderlich, Nancy; De Keyser, Arne (Journal of Business Research)
The service encounter – one of the foundational concepts in service research – is fundamentally changing due to rapid evolutions in technology. In this paper, we offer an updated perspective on what we label the “Service Encounter 2.0”. To this end, we develop a conceptual framework that captures the essence of the Service Encounter 2.0 and provides a synthesis of the changing interdependent roles of technology, employees, and customers. We find that technology either augments or substitutes service employees, and can foster network connections. In turn, employees and customers are taking on the role of enabler, innovator, coordinator and differentiator. In addition, we identify critical areas for future research on this important topic.
Keywords: Service encounter; Technology roles; Employee roles; Customer roles; Employee experience; Customer experience

Conducting Service Research that Matters. - Gustafsson, Anders; Aksoy, Lerzan; Brady, Michael K; McColl-Kennedy, Janet R; Sirianni, Nancy J; Witell, Lars; Wünderlich, Nancy (Journal of Services Marketing)
Purpose – The purpose of this paper is to encourage the reader to think differently about service-related issues and to strive to conduct service research that makes a transformational impact on individuals, organizations and society. The authors suggest that service researchers are in an excellent position to develop research that matters by making stronger connections with theory and elevating purely applied research to research that is higher in both practical relevance and methodological rigor. Design/methodology/approach – This paper takes a conceptual approach, connecting pertinent literature with new ideas highlighted in this special issue. Findings – This paper proposes that service researchers look beyond traditional service applications, take a multi-disciplinary approach to problem-solving and make greater strides towards connecting theory and practice. The authors propose a Model of Rigorous and Relevant Research, and call for fresh thinking across a wide range of research areas, including enhancing the customer experience, crafting innovation, integrating technology and measuring service outcomes. Originality/value – The originality of this essay lies in its focus on revitalizing the discussion on relevance and rigor as a path forward for service research. Additionally, this paper offers new insights on core management aspects of service provision that provide a solid platform for future work in service research.
Keywords: Relevance; Service technology; Service innovation; Customer experience; Rigor; Service outcomes

On the assessment of attitudes towards studying—development and validation of a questionnaire - Brahm, Taiga; Jenert, Tobias (Learning and individual differences : journal of psychology and education)
This research aims to develop and validate an instrument for the assessment of attitudes towards two particular objects: the Higher Education Institution (HEI) and the process of studying. Investigating attitudes towards studying at a HEI in a comprehensive way addresses an important research gap. It connects students' perception of the institution with teaching and learning. To validate the Assessment of Students' Attitudes towards Studying (ASAtS) Questionnaire, data was gathered at three different universities in Switzerland (820 students), Sweden (167) and Germany (133). Overall, the results show the internal consistency of the ASAtS. Its nomological validity is also supported by correlations with other constructs, such as intrinsic motivation and study performance. The ASAtS contributes to the theory on students learning by broadening the scope of research beyond learning in a narrow sense. From a practical point of view, it provides a tool for HE management to monitor students' perception of their HEI.
Keywords: Attitude; Student learning; Higher Education Institution; university; student experience

Adverse selection, investor experience and security choice in venture capital finance: evidence from Germany - Hartmann-Wendels, Thomas; Keienburg, Georg; Sievers, Sönke (European Financial Management (VHB-JOURQUAL 4 Ranking B))
This article analyses 336 German venture capital transactions from 1990 to 2005 and seeks to determine why selected financial securities differ across deals. We find that a broad array of financial instruments is used, covering straight equity, mezzanine and debt‐like securities. Based on the chosen financial securities’ upside potential and downside protection characteristics, we provide an explanation for the differing use of these securities. Our results show that investors’ deal experience, adverse selection risks and economic prospects in the public equity market influence the selection of financial securities.
Keywords: venture capital; capital structure; contract theory; deal experience